A CASE STUDY ON HYPOLIPIDEMIC EFFECT OF A RICE BASED MIX FORTIFIED WITH TERMINALIA ARJUNA,TRIGONELLA FOENUM- GRAECUM AND CINNAMOMUM VERUM - Borkotoky, *Priyakshi; Sarma, Bishnu Prasad (International Journal of Ayurveda and Pharma Research, 2017)
A case study is done to observe the effect of a traditional Assamese breakfast item, namely Sandohguri fortified with Vigna radiate, Terminalia arjuna, Trigonella foenum- graecum and Cinnamomum verum to incorporate hypolipidemic property. As per the nutritive value analysis, 100g of the fortified mix contains 74.75g carbohydrates, 12.92g protein, 1.07g fat (saturated fatty acids 0.30%, monounsaturated fatty acids 0.41% and polyunsaturated fatty acids 0.44%) and 7.13g dietary fibre. Main nutrients with antioxidant properties in the mix are Vitamin A (29.8 IU), Vitamin E (0.57 mg) , Vitamin C (0.16 mg), Selenium (11.2mcg ), Copper (193.4 mcg), Zinc (529.2 mcg), Iron (2531mcg) and Manganese (810.7 mcg). A hyperlipidemic patient without any other medical complications is identified and prescribed to have 90 to 100g of the mix with water/milk and sugar twice daily. A little life style modification with 30 minutes walk is also advised. The patients lipid profile is checked twice within two months from the day of using the mix. The results show an increase in high density lipoprotein (HDL) and reduction in triglyceride, cholesterol, very low density lipoproteins (VLDL)and low density lipoproteins (LDL). Furthermore, the mix is found to be helpful in minimizing various risk factors of Cardio Vascular Diseases, such as hyperlipidemia, atherosclerosis-index, body weight, body mass index and waist hip ratio.